Neospora caninum: evaluation of vertical transmission in slaughtered dairy cows (Bos taurus) Neospora caninum: avaliação da transmissão vertical em vacas leiteiras (Bos taurus) - César Augusto Barbosa de Macedo; Madlaine Frigo Silveira Barbosa de Macedo; Sergio Tosi Cardim; Milaine Cristiane Dantas Custódio Paiva; Alessandra Taroda; Luiz Daniel Barros; Ivo Alexandre Leme da Cunha; Dauton Luiz Zulpo; João Luis Garcia (Revista Brasileira de Parasitologia Veterinária, 2013)
Neospora caninum is a worldwide parasite recognized as one of the main parasites responsible for abortion in cattle. The objective of this study was to evaluate vertical transmission of N. caninum in dairy cows (Bos taurus) that were slaughtered at an abattoir in the state of Santa Catarina, southern Brazil. Blood samples (with and without EDTA) from 60 pregnant dairy cows and blood and tissue samples (brain, lung, heart and liver) from their fetuses were collected and used for PCR and serological evaluation. Blood samples from 60 non-pregnant cows were collected and used to detect antibodies. Anti-N. caninum antibodies were detected by indirect ELISA. Antibodies against N. caninum were observed in 41.6% (25∕60) of the pregnant cows and in 43.3% (26∕60) of the non-pregnant cows. Antibodies against the parasite were detected in sera from three fetuses (5.5%). PCR analysis revealed that 3.3% (2∕60) of the cows and 6.6% (4∕60) of the fetuses evaluated were positive for specific N. caninum primers. These positive fetuses were between 4-6 months of age. Therefore, considering PCR and serological tests to be indicative of vertical transmission in fetuses, 11.6% (7∕60) of the fetuses were infected by N. caninum during gestation. Neospora caninum é um parasita de distribuição mundial reconhecido como um dentre os principais parasitas, responsável por abortamento em bovinos. O objetivo deste estudo foi avaliar a transmissão vertical de N. caninum em vacas leiteiras (Bos taurus) que foram submetidas ao abate em matadouro no Estado de Santa Catarina, sul do Brasil. Sangue (com e sem EDTA) de 60 vacas leiteiras prenhas e amostras de sangue e tecidos (cérebro, pulmão, coração e fígado) de seus fetos foram coletados e utilizados para PCR e avaliação sorológica. Amostras de sangue de 60 vacas não-gestantes foram obtidas e utilizadas para detecção de anticorpos. A detecção de anticorpos séricos anti-N. caninum foi avaliada pelo ELISA-teste indireto. Anticorpos anti-N. caninum foram observados em 41,6% (25∕60) das vacas prenhas e em 43,3% (26∕60) das vacas não-gestantes. Três fetos (5,5%) foram soros positivos para N. caninum. Análise pela PCR revelou que 3,3% (2∕60) das vacas e 6,6% (4∕60) dos fetos avaliados foram positivos para N. caninum. As idades dos fetos positivos eram de 4 a 6 meses. Portanto, considerando a PCR e a sorologia como indicativo de transmissão vertical em fetos, 11,6% (7∕60) dos fetos foram infectados por N. caninum durante a gestação.